2023
DOI: 10.3390/en16135053
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Nanoparticle-Decorated Fused Carbon Sphere Composite as a Catalyst for Hydrogen Generation

Abstract: The dwindling supply of fossil fuels has resulted in a search for an efficient alternative energy source. Hydrogen gas offers an abundant, clean-burning supply of energy that can be readily produced over time via the water-splitting reaction of sodium borohydride (NaBH4). This study explored the synthesis of a novel catalyst comprised of silver nanoparticles supported on fused carbon spheres (AgNP-FCS). This composite catalyst was then tested for its ability to optimize the hydrolysis reaction of NaBH4. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Once there are no more hydrogen atoms for water to attack, the remaining tetrahydroxyborate [B(OH)4] can unbind from the copper nanoparticle and a new BH4 -can take its place, repeating the cycle. Finally, the graphene-like materials (GLMs) used in this study showed great promise as catalyst support with agreement with other studies [67][68][69].…”
Section: Resultssupporting
confidence: 90%
“…Once there are no more hydrogen atoms for water to attack, the remaining tetrahydroxyborate [B(OH)4] can unbind from the copper nanoparticle and a new BH4 -can take its place, repeating the cycle. Finally, the graphene-like materials (GLMs) used in this study showed great promise as catalyst support with agreement with other studies [67][68][69].…”
Section: Resultssupporting
confidence: 90%
“…al. (1985) and also by Grzeschik et al (2020), and in previous work by this research team [ 11 , 12 , 13 , 14 , 33 , 34 , 35 , 36 , 37 ]. It may be that hydroxide ions compete for hydrogen in the solution.…”
Section: Resultssupporting
confidence: 55%
“…This reaction, however, occurs relatively slowly and requires a catalyst to improve the generation rate of hydrogen [ 3 ]. In recent years, precious metal nanoparticles have been utilized for a variety of different applications including gas detection [ 4 ], anti-bacterial properties [ 5 ], optoelectrical properties [ 6 ], as catalysts [ 7 , 8 ], and for hydrogen generation [ 9 , 10 ], including as a catalyst for the hydrolysis of NaBH 4 [ 11 , 12 , 13 , 14 ]. Gold nanoparticles, for instance, are used as catalysts in various chemical reactions.…”
Section: Introductionmentioning
confidence: 99%